ANALYSIS OF THE EMOTIONAL BEHAVIOR OF USERS OF SITES BASED ON NEURAL NETWORKS - Nikitin, Danila; Lobarev, Dmitry (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
Create a neural network capable of predicting the emotional coloring of a comment.